2019
DOI: 10.32479/irmm.8113
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Strategy of Pt. Bandara Internasional Jawa Barat Bandung Indonesia, Kertajati in Business Aerocity (Aerotropolis)

Abstract: Aerotropolis is a city airport development concept, or commonly called "Airport City." The concept of aerotropolis is a new concept in the world transport industry where the Airport has shifted from transportation center to a multifunctional aero metropolis. The development of an international airport can be a trigger for business development as well as the surrounding urban areas. The airport city serves not only as a performance index of a State in development but also plays a role as a driver of national in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…The results of Goteborg's research (2007) found that the objective of a marketing strategy is that program implementation in achieving organizational goals can be done actively, consciously, and rationally, about the achievement of a business product achieving its objectives in an increasingly turbulent business environment. Syafarudin and Mulyana (2019) states that then the characteristics of service strategy management are as follows (Kumar, 2002):…”
Section: Service Strategy Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Goteborg's research (2007) found that the objective of a marketing strategy is that program implementation in achieving organizational goals can be done actively, consciously, and rationally, about the achievement of a business product achieving its objectives in an increasingly turbulent business environment. Syafarudin and Mulyana (2019) states that then the characteristics of service strategy management are as follows (Kumar, 2002):…”
Section: Service Strategy Managementmentioning
confidence: 99%
“…Syafarudin and Sudiarditha (2018) states that public services are activities carried out by a person or group of people on the basis of material factors through certain systems, procedures and methods in an effort to meet the interests of others in accordance with their rights. Then Syafarudin and Mulyana (2019) states that the purpose of public services is to prepare those public services that are desired or needed by the public, and how to state correctly to the public about their choices and how to access them that are planned and provided by the government (Flynn et al, 2010). states that emergency response plans must carry out communication and outreach with a good strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Research journals conducted by Badjuri (2013), Darmawan et al (2015), andMa'mun et al (2017) explain that motivation is a collection of behaviors that provide an employee foundation for working hard. Newstrom (2011) and Syafarudin (2019) state that work motivation is the result of a collection of internal and external forces that cause workers to choose the right path of action and use certain behaviors. According to Mathis and Jackson (2006), motivation is the desire in a person that causes the person to act.…”
Section: Motivationmentioning
confidence: 99%
“…According to Herzberg cited in Hasibuan (2007), which are classified as motivational factors include: responsibility, appreciation, work itself, and development and progress. Syafarudin (2019) stated that besides the intrinsic motivation dimension, there is another dimension, namely the extrinsic dimension. In contrast to the intrinsic dimension, where if the intrinsic dimension comes from within each individual, the extrinsic dimension comes from outside the individual itself.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation